Jaranol: a compound with therapeutic activity against pathological cardiac remodelling via multi-target inhibition of the Snai3/TLR2 and NF-κB signaling pathways - Zhang, Yao; Li, Nan; Chu, Shiqi; Fu, Heqing; Yang, Xiaowen; Xia, Huimin; Xiao, Yunfeng; Xiao, Zhibin; Liu, Jing; Dong, Yu; Liu, Tianlong (Frontiers in Pharmacology, 2026)
Inhibiting pathological cardiac remodelling is considered an important therapeutic approach for heart failure, although effective strategies are still lacking in the clinic. Jaranol was found to be widely distributed in Chinese herbal medicine with multi biological functions, however, its effects on pathological cardiac remodelling remain unexplored. The present study identified the potential therapeutic effects of jaranol on cardiac remodelling base-joint analysis of the serum proteomic profile of patients with heart failure and Astragalus membranaceus-related potential targets. Jaranol treatment ameliorated angiotensin II (Ang II)- and transverse aortic constriction (TAC)-induced pathological cardiac remodelling in vitro and in vivo, as evidenced by the improved cardiac function, hypertrophy and fibrosis. The mRNA-sequencing and biochemical analyses showed that Toll-like receptor (TLR) signaling and TLR2 expression were suppressed in myocardial tissue after jaranol treatment. Mechanistically, jaranol enhanced the expression of transcription factor Snai3, leading to decreased expression of TLR2 in myocardium, meanwhile, adding Snai3 protein to culture media could suppressed TLR2 expression in neonatal mouse primary cardiomyocytes. Proteome microarray assays indicated that jaranol could interact with NF-κB, a key regulatory factor of the TLR signalling pathway. Indeed, jaranol suppressed the Ang II-induced translocation of NF-κB from the cytoplasm to the nucleus in human induced pluripotent stem (hiPS)-cardiomyocytes. In conclusion, the present study demonstrated a novel role of jaranol in preventing pathological cardiac remodelling via multi-target inhibition of Snai3/TLR2 and NF-κB signaling pathways.